Integration and Disintegration in European Societies – Identity and Social Issues at the time of the Globalization of Cultures and Economical crisis - Drwęski, Bruno (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
This article tries to redefine the concept of multiculturalism as a potentially dynamic one, in a situation where this word is mainly used to qualify visible differences between ethnical or religious groups, not taking into account the fact that, historically, different national or religious groups developed different political cultures and social programmes that helped humankind to progress. At the time of globalisation, we observe the impoverishment of religions, ideologies and nations as carriers of alternative values and this created a situation blocking human progress, creating then frustrations and tensions between groups reduced to their visible differences and all submitted to the same dominant culture.
Keywords: culture; ethnicity; multiculturalism; nation; postmodernity; progress; religion